Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmicb.2021.780768
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Causes Mitochondrial Dysfunction and Mitophagy Impairment

Abstract: Mitochondria, which is essential for adequate innate immune response, energy metabolism and mitochondria reactive oxygen species (ROS) production, might be in the cross fire of Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and host cell defense. However, little is known about interactions between mitochondria and SARS-CoV-2. We performed fluorescent microscopy and found an enrichment of SARS-CoV-2 replication products double stranded RNA (dsRNA) within mitochondria. The entry process of dsRNA mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 34 publications
9
89
0
Order By: Relevance
“…Recently, an innovative biochemical approach showed a physical and functional interaction between SARS-CoV-2 and host mitochondria [12]. These findings were also supported by imaging approaches using SARS-CoV-2-infected cells [13]. However, the absence of images visualizing the interaction between SARS-CoV-2 and mitochondria in tissues from patients with COVID-19 remains a critical gap.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, an innovative biochemical approach showed a physical and functional interaction between SARS-CoV-2 and host mitochondria [12]. These findings were also supported by imaging approaches using SARS-CoV-2-infected cells [13]. However, the absence of images visualizing the interaction between SARS-CoV-2 and mitochondria in tissues from patients with COVID-19 remains a critical gap.…”
Section: Introductionmentioning
confidence: 89%
“…A negative control was obtained by omitting the primary antibody and using only the secondary gold-conjugate antibody. The control of immunogenicity of antibodies primary versus nucleocapsid protein of SARS-CoV-2 was assumed from Shang C. et al [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…They also showed that the virus can disrupt the binding of the LIR domain of P62 protein with LC3 protein. This lowers the cell’s ability to ubiquitinate seized mitochondria, which blocks mitophagy, resulting in disrupted mitochondrial homeostasis and lowered viral RNA degradation [ 218 ].…”
Section: Mitochondriamentioning
confidence: 99%